2013
DOI: 10.1515/jpem-2012-0170
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor expression in whole blood with preterm infants

Abstract: Importantly, in preterm infants, both the expression of GRβ and the GRα/GRβ ratio were associated with birth weight. Further studies with larger populations are necessary to determine the relation between the expression of GR and the clinical relevance of preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Several polymorphisms in the glucocorticoid receptor gene (NR3C1) are linked to altered function of glucocorticoid receptor. SNPs may increase glucocorticoid sensitivity in vivo , and have been associated with birth weight in preterm neonates [62] , [63] .…”
Section: Discussionmentioning
confidence: 99%
“…Several polymorphisms in the glucocorticoid receptor gene (NR3C1) are linked to altered function of glucocorticoid receptor. SNPs may increase glucocorticoid sensitivity in vivo , and have been associated with birth weight in preterm neonates [62] , [63] .…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative reverse transcriptase polymerase chain reaction (RT-qPCR) was performed using the TaqMan method. The sequences of the primers and probes used for GRα were designed to span exons 8 and 9α, the specific sequence for GRα, as previously described [12, 22]: GRα-F 5′-TTGGATTCTATGCATGAAGTGGTT-3′, GRα-R 5′-CAATACTCATGGTCTTATCCAAA­AA­TG-3′, and GRα-probe FAM-TCTCCTTAACTATTGCTTCCA-TAMRA. The primers and probes for GRβ and actin beta (ACTB) were purchased from ABI (Applied Biosystems, Foster city, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies reported a change in the GC receptor (GR) expression pattern, which is essential for regulating the transcription of GC-responsive genes in the perinatal period [12]. GC activity is mediated by GR, an intracellular receptor protein, which belongs to the nuclear receptor superfamily and regulates the expression of GC-responsive genes [13, 14].…”
Section: Introductionmentioning
confidence: 99%